Macroeconomic Determinants of the Entrepreneurial Activity at Different Business Cycle Phases - Antsygina, Anastasia Leonidovna; Zhukov, Aleksey Nikolaevich; Sypchenko, Anastasia Evgenyevna (Economy of Regions, 2017)
Nowadays, the Russian economy is facing the crisis. Thus it becomes important to create a favorable environment for the formation of local sustainable economic growth and positive expectations in the business sector. The existing literature in this field focuses on macroeconomic determinants of the entrepreneurial activity and does not investigate the effect of the business cycle on firms’ decision making. On the contrary, this paper concentrates on Russian regions and identifies the key business cycle factors shaping the entrepreneurial activity both at the regional and the firm-specific levels. The analysis combines aggregate series on 83 regions in 2005-2014 with microeconomic data provided by “SPARK-Interfax”. In particular, we considered 200 companies in 4 regions of Russia during 2005-2014. Special attention is paid to testing of research hypotheses concerning dynamics of enterprise activity on various phases of business cycle. The identification strategy is built on panel data analysis, as well as survival analysis. We find that the aggregate entrepreneurial activity responds to changes in the regional economic environment with a lag. Moreover, it shows some acyclicity. On average, firms that were organized during the downward phase of the business cycle are more stable (i.e. have a high survival rate). This can be explained with a stronger financial resistance and their experience of operating under uncertainty. Based on these findings, we formulate policy recommendations. In particular, we propose to develop a regional “business map” that would reflect the key features of Russian territories.